Anthropogenic Perturbations to the Atmospheric Molybdenum Cycle. Issue 2 (22nd February 2021) - Wong, Michelle Y.; Rathod, Sagar D.; Marino, Roxanne; Li, Longlei; Howarth, Robert W.; Alastuey, Andres; Alaimo, Maria Grazia; Barraza, Francisco; Carneiro, Manuel Castro; Chellam, Shankararaman; Chen, Yu‐Cheng; Cohen, David D.; et al.
Abstract: Molybdenum (Mo) is a key cofactor in enzymes used for nitrogen (N) fixation and nitrate reduction, and the low availability of Mo can constrain N inputs, affecting ecosystem productivity. Natural atmospheric Mo aerosolization and deposition from sources such as desert dust, sea‐salt spray, and volcanoes can affect ecosystem function across long timescales, but anthropogenic activities such as combustion, motor vehicles, and agricultural dust have accelerated the natural Mo cycle. Here we combined a synthesis of global atmospheric concentration observations and modeling to identify and estimate anthropogenic sources of atmospheric Mo. To project the impact of atmospheric Mo on terrestrial ecosystems, we synthesized soil Mo data and estimated the global distribution of soil Mo using two approaches to calculate turnover times. We estimated global emissions of atmospheric Mo in aerosols (<10 μm in diameter) to be 23 Gg Mo yr −1, with 40%–75% from anthropogenic sources. We approximated that for the top meter of soil, Mo turnover times range between 1, 000 and 1, 000, 000 years. In some industrialized regions, anthropogenic inputs have enhanced Mo deposition 100‐fold, lowering the soil Mo turnover time considerably. Our synthesis of global observational data, modeling, and a mass balance comparison with riverine Mo exports suggest that anthropogenic activity has greatly accelerated the Mo cycle, with potential to influence N‐limited ecosystems. Plain Language Summary: Molybdenum (Mo) is an essential trace element that is, important for terrestrial and aquatic ecosystems, as it is required for biological nitrogen fixation and uptake. Mo is carried in particles to the atmosphere from sources such as desert dust, sea spray, and volcanoes resulting in losses and sources to different ecosystems. Atmospheric Mo deposition is essential on long time scales for soils which have lost Mo due to soil weathering, with consequences for nitrogen cycling. Anthropogenic changes to the Mo cycle from combustion, motor vehicles, and agricultural dust, are likely to be large, and have more than doubled sources of Mo to the atmosphere. Locally, anthropogenic changes to Mo in industrialized regions can represent a 100‐fold increase in deposition, and may affect nitrogen cycling in nitrogen‐limited ecosystems. Key Points: We compiled atmospheric molybdenum (Mo) concentration data and compared observations to a three‐dimensional global atmospheric aerosol model Anthropogenic activity has likely doubled atmospheric Mo globally, but with regional variation Mo turnover time in soils ranges between 1, 000 and 1, 000, 000 years, with the shortest times in dust source regions and industrialized areas